2019
DOI: 10.1007/978-1-0716-0211-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Deducing the Crystal Structure of MERS-CoV Helicase

Abstract: RNA virus encodes a helicase essential for viral RNA transcription and replication when the genome size is larger than 7 kb. Coronavirus (CoV) has an exceptionally large RNA genome (~30 kb) and it encodes an essential replicase, the nonstructural protein 13 (nsp13), a member of superfamily 1 helicases. Nsp13 is among the evolutionary most conserved proteins not only in CoVs but also in nidovirales. Thus, it is considered as an important drug target. However, the high-resolution structure of CoV nsp13 remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Helicase enzyme in coronavirus is a prominent viral replication enzyme. Helicases are evolutionarily conserved proteins in coronaviruses and Nidovirales [27]. Furthermore, double-stranded nucleic acids are separated into two single-stranded nucleic acids by helicases, which catalyse the separation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Helicase enzyme in coronavirus is a prominent viral replication enzyme. Helicases are evolutionarily conserved proteins in coronaviruses and Nidovirales [27]. Furthermore, double-stranded nucleic acids are separated into two single-stranded nucleic acids by helicases, which catalyse the separation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interaction with epigenetic, gene regulatory pathways and cytoskeleton was shown [ 3 ]. The crystal structure was resolved recently for the MERS-CoV virus [ 110 ] and study of the crystal composed of the SARS-CoV-2 holo-RdRP and NSP13 confirmed that a stable complex could be formed [ 98 ]. The interaction of the two proteins is thought to be mediated by the ZBD domain of SARS-CoV-2 NSP13 and the extension of the NSP8 subunit.…”
Section: Structure and Function Of The Sars-cov-2 Rna Polymerase: Thementioning
confidence: 99%
“…As a member of the SF1B helicase family, nsp13 unwinds RNA or DNA duplexes with 5'-to-3' directionality and hydrolyzes both NTP and dNTP (7,8); it also hosts 5'triphosphatase activity. In previous work, by determining the crystal structure of MERS-CoV nsp13 (PDB ID: 5WWP), we revealed that nsp13 generally mirrors the domain organization of nidovirus helicases, whereas the individual domains (i.e., CH, RecA1-1B and RecA2) of nsp13 reflect the organization of cellular Upf1-like helicases (9,10).…”
Section: Introductionmentioning
confidence: 96%